A Patient of Using Presepsin to Diagnose Streptococcal Toxic Shock Syndrome during Anticancer Drug Treatment - Gaku Takahashi (Case Reports in Critical Care)
Background. Streptococcal toxic shock syndrome (STSS) is a rapidly progressive infection, with potentially rapid patient deterioration in a very short period. We experienced a rare case of STSS during anticancer chemotherapy, and we continuously measured presepsin (P-SEP) and evaluated its usefulness. Case Presentation. A 60-year-old woman with pulmonary metastasis from cervical cancer began anticancer chemotherapy. A fever of >40°C and right lower leg swelling developed on day 3. Symptoms worsened despite cefmetazole treatment (1.0 g/day). Blood culture was performed without suspecting STSS. On day 5, symptoms worsened and acute disseminated intravascular coagulation (DIC) and sequential organ failure assessment (SOFA) scores increased. C-reactive protein (CRP) increased from 28.8 mg/dl to 35.5 mg/dl and P-SEP also increased from 1,635 to 2,350 pg/mL. STSS was suspected due to the rapid progression of brown discoloration of the entire right lower leg. Ceftriaxone 2 g/day and clindamycin 1,200 mg/day were begun. On the evening of day 5, blood culture revealed rapidly progressive group A streptococci. After that, symptoms improved rapidly with treatment, and SOFA and DIC scores also decreased. While CRP remained at about 0.5 mg/dl, P-SEP remained slightly elevated at about 400 pg/mL. A residual infection focus was suspected. Contrast-enhanced computed tomography (CT) revealed a capsule-enclosed abscess in the right lower leg soleus muscle on day 32. Debridement was performed and antibiotics were continued until P-SEP was 88 pg/mL. CT confirmed the disappearance of the abscess. Conclusion. Prompt diagnosis by blood culture and a sufficiently early, appropriate change in antibiotic therapy led to successful recovery from STSS during anticancer chemotherapy without lower limb amputation. P-SEP was useful in assessment of the residual infection focus and suspending treatments.